SOME OBSERVATIONS OF LANDSLIDES TRIGGERED BY THE 29 APRIL 1991 RACHA EARTHQUAKE, REPUBLIC OF GEORGIA - Jibson R.W.; Prentice C.S.; Borissoff B.A.; Rogozhin E.A.; Langer C.J. (My University, 1994)
On 29 April 1991 an Ms 7.0 earthquake occurred in the Racha region of the Great Caucasus Mountains in north-central Republic of Georgia. The earthquake occurred on a thrust fault striking roughly east-west and dipping about 20 ° to 45 ° northward; focal depth was 17 ---2 km. We observed no surface fault rupture, but the earthquake caused extensive structural damage to the many unreinforced stone buildings in the area, and at least 114 people were killed. Many landslides were triggered in a 2500-km ~ epicentral area, and they caused much of the structural damage and at least half the fatalities. We observed the following six types of landslides (in order of decreasing abundance): rock falls, debris slides, slumps, earth slides, rock block slides, and rock avalanches. The types of landslides triggered by the earthquake are controlled primarily by li-thology and geologic structure. Enigmatic landslide processes associated with this earthquake include (1) delays of several days between earthquake shaking and significant landslide movement, probably caused by changes in ground-water conditions; (2) small co-seismic displacement of landslides active at the time of the earthquake, a possible result of viscoplastic damping of the seismic shaking; and (3) somewhat unusual failure geometries related to local topog-raphy and geologic structure.